2007
DOI: 10.1007/bf03021709
|View full text |Cite
|
Sign up to set email alerts
|

Technical report: Optimal quantity of saline for epidural pressure waveform analysis

Abstract: Purpose: Epidural waveform analysis (EPWA) is a simple test to confirm the optimal placement of an epidural catheter. It relies on the transmission of the thecal pressure waveform through the epidural catheter. Little is known about the optimal volume of catheter injectate needed to optimize the EPWA test. Methods:In a randomized controlled trial we compared three different catheters: stimulating, open-ended hole [S1]; stimulating, three-hole [S3]; non-stimulating three-hole [NS3]) in 60 patients in an unblind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…1 Although the sensitivity of EWA through the needle exceeds that of the catheter, 9 most trials have focused on catheter EWA. [10][11][12] In 2006, Lennox et al 9 assessed pulsatile waveforms through the epidural needle after obtaining LOR. These authors reported 97.5% sensitivity, 100% specificity, 100% positive predictive value, and 50% negative predictive value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Although the sensitivity of EWA through the needle exceeds that of the catheter, 9 most trials have focused on catheter EWA. [10][11][12] In 2006, Lennox et al 9 assessed pulsatile waveforms through the epidural needle after obtaining LOR. These authors reported 97.5% sensitivity, 100% specificity, 100% positive predictive value, and 50% negative predictive value.…”
Section: Resultsmentioning
confidence: 99%
“…We speculate that false-negative waveforms were due to the administration of suboptimal volumes of normal saline through the epidural needle before EWA. Our protocol used a 5-mL volume based on the findings of de Médicis et al 12 These authors advocated 5-mL injectates because of the minimal differences seen between 5, 7.5, and 10 mL; however, 5-mL volumes yielded positive waveforms in only 90% of their subjects. 12 Thus, we hypothesize that, in clinical practice, the rate of false-negative waveforms could be decreased with higher injectates of normal saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our protocol employed a 5 ml saline injection through the epidural needle before waveform analysis, based on the findings of de M edicis et al [15]. These authors observed minimal differences between 5, 7.5 and 10 ml; however, 5-ml volumes yielded positive waveforms in only 90% of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14][15] However, due to false-positive waveforms, block failure remains a possibility despite EWA. 9 Furthermore, falsenegative waveforms may lead to unnecessary attempts and a higher rate of dural puncture or vascular breach.…”
Section: Discussionmentioning
confidence: 99%